Beatrice: A Study in the Creation and Destruction of Value - BAKER, GEORGE P. (Journal of Finance, 1992)
ABSTRACT This paper chronicles the history of the Beatrice company from its founding in 1891 as a small creamery, through its growth by acquisition into a diversified consumer and industrial products firm, and its subsequent leveraged buyout and sell‐off. The paper analyzes the value consequences the firm's acquisition and divestiture policies, its organizational strategy, and its governance. The analysis sheds light on a number of issues in organization theory, strategy, and corporate finance, including the sources of value in diversifying aquisitions, the cost of over‐centralization and weak corporate governance, and the mechanisms of value creation in the market for corporate control.